Electrocatalytic Study at Silver/Polypyrrole Nanowires Composite Modified Electrodes - LING ZHANG*, XIU; XIN XING†, JIAN; JIN‡, FENG (Asian Journal of Chemistry, 2024)
Silver modified composite electrodes were prepared by electrochemicalmethod on the polypyrrole (PPy) nanowires modified electrodes.The surface behaviour of it was investigated by scanning electronicmicroscopy and energy-dispersive X-ray analysis (EDX). The electrocatalyticactivity of it was characterized by electroreduction of nitrateand their reduction products. The effect of solution pH, electrolyticpotentials and electrolytic current density on nitrate electrolysis and theproduct were also examined. The experimental results indicate that Ag/PPy nanowires composite modified electrodes have higher catalyticactivity toward nitrate reduction, the nitrite and ammonia in the resultedsolution products are always at low concentration. This result showsthat the electrodes have promising application in environmentalremediation.